PJOK learning model through playing activities to build student character: designing and developing stage - Mhd. Ashar; Syafruddin Syafruddin; Gusril Gusril; Eri Barlian (International Conferences on Educational, Social Sciences and Technology)
One effort that can be done to overcome the deterioration of character values is through PJOK education. PJOK learning model was deemed necessary to be developed so that learning can build character values. The preliminary study data were collected by using questionnaires and interviews, then analyzed using descriptive statistics and descriptive analysis. The preliminary study results show that the average test score from 50 students is 60.50 point with five sets of test materials, playing at school 60 point, playing outside of school 50 point, learners participation at play time 40 point, character of awake learners 30 point and problem faced when playing 70. The value of such data can be categorized very low and the authors conclude that it is necessary to design a learing model of sport and health education subject to construct character value of elementary school students. Based on the results of preliminary studies the authors try to design and develop PJOK learning model through playing activities to build student character values. The type of research used is Research and Development (R&D) with procedure is Analyze, Design, Development, Implementation, Evaluation (ADDIE).